Strengthening Nationalism at the Indonesia-Malaysia Border Community through Civic Education, Case Study on Sebatik Island, Nunukan Regency, North Kalimantan Province - ., Wahyudi; Nanik Setyowati, RR; ., Harmanto; ., Listyaningsih (KnE Social Sciences, 2024)
This study aims to know, analyze, and formulate the strengthening of nationalism for the border community on Sebatik Island, Nunukan Regency, North Kalimantan Province through citizenship education. Sebatik Island is one of Indonesia’s border areas located in Nunukan Regency, North Kalimantan Province, which is directly adjacent to Sabah, Malaysia. The development gap between the country’s border areas shapes the attitudes and behaviors of Sebatik border communities, who have the preference to use foreign currency, consume foreign products, and have dual citizenship. This research uses a qualitative approach with a case study method. Data were obtained from in-depth interviews, observations, and documentation studies. The results showed that civic education in schools can contribute to strengthening nationalism through school-based civic education and community-based citizenship education which is carried out among others by lecture methods, socialization of national insight, habituation, field action, and involvement in basic military training organizations. The recommendations of this research can be used as a role model in strengthening the nationalism of Indonesian society, especially in border areas. Keywords: nationalism, border, Sebatik Island, civic education, citizenship education